2003
DOI: 10.1359/jbmr.2003.18.9.1642
|View full text |Cite
|
Sign up to set email alerts
|

Association of Molecular Variants, Haplotypes, and Linkage Disequilibrium Within the Human Vitamin D-Binding Protein (DBP) Gene With Postmenopausal Bone Mineral Density

Abstract: Introduction: Osteoporosis results from the interplay of multiple environmental and genetic determinants. The gene encoding vitamin D-binding protein (DBP), a key factor for regulating calcium homeostasis through the vitamin D endocrine system, is a probable candidate for conferring susceptibility to osteoporosis. Methods: To test a possible contribution of the DBP gene for determination of bone mineral density (BMD) of adult women, we have characterized 13 single nucleotide polymorphisms (SNPs) within the DBP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 34 publications
(80 reference statements)
1
27
1
Order By: Relevance
“…The CYP24A1 gene codes for 24(OH)ase, which degrades 1,25(OH) 2 D. The potential for the SNPs we examined to alter DBP or CYP24A1 function is possible but has not been studied. Some studies have suggested a relationship of these SNPs with other outcomes, including asthma, glucose tolerance, and bone mineral density [33-35]. We are not aware of any studies that examined these SNPs in relation to breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The CYP24A1 gene codes for 24(OH)ase, which degrades 1,25(OH) 2 D. The potential for the SNPs we examined to alter DBP or CYP24A1 function is possible but has not been studied. Some studies have suggested a relationship of these SNPs with other outcomes, including asthma, glucose tolerance, and bone mineral density [33-35]. We are not aware of any studies that examined these SNPs in relation to breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…While most studies have focused on the two major SNPs (rs7041 and rs4588) seen in Caucasians and people of African descent, Ezura et al examined 13 DBP polymorphisms in a cohort of 384 postmenopausal Japanese women [12]. Five of these variants were significantly associated with BMD; one of these SNPs (−39 C > T ) was found in the promoter region, while the remainder were intronic.…”
Section: Dbp Polymorphisms and Bone Healthmentioning
confidence: 99%
“…The DBP may also have a role in inflammation and the immune system (76). Ezura et al (38) characterized a C/T polymorphism at position −39 in the Gc promoter region that was strongly linked to bone mineral density. Kidd et al (73) identified two of three SNPs in the Gc promoter region with functional effects on transcription factor binding sites.…”
Section: Vitamin D-binding Protein (Gc)mentioning
confidence: 99%